The Succesful of Student Well-Being Development Through Child-Friendly School Programs - Mangestuti, Retno; Mulyadi, Mulyadi; Wahyuni, Esa Nur; Aziz, Rahmat; Qudzy, Saifuddin Zuhri (Universitas Pendidikan Ganesha, 2022)
The paradigm shift in education has stimulated the emergence of new issues regarding the focus of education, including student wellbeing. The well-being of students at school will have a significant impact on their academic success and socio-emotional and health development. One of the efforts to improve student welfare is the child-friendly school program. This study aims to analyze the success of child-friendly schools in developing student welfare by using the method of observation and interviews with principals, vice-principals, teachers, and academic staff in one of the elementary schools. The data were analyzed using theme analysis techniques. The results of this study indicate that a school model that can develop student welfare is a school that, in the process of its implementation, there is a learning pattern that favors students, a pattern of humanistic social relations among school residents, as well as environmental support and infrastructure that is friendly to students. This study implies that policies in educational practice must be able to cloud the implementation of child-friendly schools, which can be a solution to developing student wellbeing.